Isolation and detection of rotavirus by Enzyme linked Immune assay in fecal specimens of buffalo calves - Khalaf, Ahmed Saadi; Aldoori, Atheer (The Iraqi Journal of Veterinary Medicine, 2019)
A total of 50 fecal samples were collected from buffalo calves ages between 3 days to 4 months, in middle area of Iraq (Baghdad, Salahaldden, Babylon, Diyala, and Wasit) between July 2016 to June 2017. All samples were examined by Immuno-chromatographic rapid tests for detection of buffalo rotavirus, twenty samples were positive. Enzyme-Linked Immunosorbent Assay. test was also used and revealed only 8 positive samples, the later samples were used for viral isolation on fetal bovine kidney cell culture for detection the cytopathogenic effects of the virus. The cytopathogenic effects of virus were induced rounded cells and gaps; as a result of rupture of these infected cells by rotavirus. Moreover Enzyme-Linked Immunosorbent Assay test used again for detection of rotavirus cytopathogenic effect in fetal bovine kidney cell culture for more confirmation. The TCID 50 was estimated for rotavirus on fetal bovine kidney cells 104.5 virus/0.05 ml